Faktor-Faktor yang Mempengaruhi Kebakaran Hutan di Indonesia dan Implikasi Kebijakannya - S. Andy Cahyono; Sofyan P. Warsito; Wahyu Andayani; Dwidjono H. Darwanto (Department of Forestry, Faculty of Agriculture, University of Lampung, 2015)
Forest fire is one of the crucial environmental and forestry issues as well as local and global concern. The longstanding efforts have been conducted to overcome this problem, but the success was relatively low. This study aims to determine the factors that affect the extent of forest and peat fires in Indonesia. The analysis of forest fires was carried out on three major islands, i.e. Sumatra, Kalimantan and Papua using time series data from 1969 to 2012. The data were analyzed using econometric models. The results indicated that the factors affecting the forest and peat fires included the price of logs, export prices of CPO, el nino, budget of the Ministry of Forestry, the economic crisis and the number of hotspots. The identified determinant which has a major impact on the extent of forest and peat fires is the number of hotspots. Controlling the number of hotspots significantly reduced the magnitude of forest fires. For that reason, there is a need for a paradigm shift in the control of forest fires from forest fire fighting activities into preventive effort by reducing the number or preventing the occurrence of hotspots as an early indication of a forest fire. Keywords: forest fires, hotspots, prevention